Molecular docking study of mutant levansucrase (E342A) from Bacillus subtilis as a receptor for D-glucopyranose and β-D-fructofuranose ligands: Molecular docking study of mutant levansucrase - Diah Miftahul Aini; Firda Ade Irmayanti; Emmy Yuanita; Maulida Septiyana; Baiq Desy Ratnasari (Acta Chimica Asiana, 2025)
Molecular docking is a widely applied computational approach for predicting the binding modes of small-molecule ligands within the active site of a target protein. This research investigated the interactions of mutant levansucrase E342A from Bacillus subtilis (PDB ID: 1PT2) for β-D-fructofuranose and D-glucopyranose ligands. Using AutoDock Vina, the docking results indicated that β-D-fructofuranose exhibited a higher binding energy of –5.6 kcal/mol, compared to D-glucopyranose with a value of –5.4 kcal/mol, suggesting a more stable interaction. It was supported by the binding interaction analysis of β-D-fructofuranose, which established five hydrogen bonds, including direct interactions with the key catalytic residues Asp86 (2.76 Å) and Asp247 (2.64 Å) that are essential for the enzymatic reaction. In contrast, D-glucopyranose formed four hydrogen bonds, involving Arg360 (3.07 Å) and Glu340 (2.64 Å), with most residues contributing to structural stabilization rather than direct catalysis. These results confirm that β-D-fructofuranose plays a crucial role as a determinant of levansucrase activity in the biosynthesis of levan-type FOS, which are known to exhibit strong prebiotic activity.